Cathodic Determination of Tobacco-Specific Nitrosamines in the Presence of 4-Nitroquinoline-N-Oxide. A Theoretical Insight. - Lyudmyla V. Romaniv (Letters in Applied NanoBioScience. Volume 14, Issue 3, 2025, 8 Р., 2025)
In this work, the possibility of electroanalytical determination of tobacco-specific nitrosamines (TSN) in the presence of 4-nitroquinoline N-oxide (NQO) was described theoretically for the first time. Electroanalytical detection will be performed by a cathodic process, assisted by vanadium oxyhydroxide, allowing the reduction of NQO by the nitric and N-oxide groups and of TNS by the nitrosamine group. Both processes correspond to reduction peaks, through which it is possible to detect and quantify the concentration of these compounds. The theoretical analysis of the electroanalytical process confirms the effectiveness of vanadium oxyhydroxide for the detection of TNS in the presence of NQO, maintaining the linear dependence between the electrochemical parameter and the concentration in a wide range of parameters.
Keywords: smoking; tobacco-specific nitrosamines; 4-nitroquinoline N-oxide; vanadium oxyhydroxide; electrochemical sensors; electrochemical oscillations; stable steady state.